2014
DOI: 10.1038/ncomms6809
|View full text |Cite
|
Sign up to set email alerts
|

Targeting β-catenin signaling for therapeutic intervention in MEN1-deficient pancreatic neuroendocrine tumours

Abstract: Inactivating MEN1 mutations are the most common genetic defects present in sporadic and inherited pancreatic neuroendocrine tumours (PNETs). The lack of interventional therapies prompts us to explore the therapeutic approach of targeting β-catenin signalling in MEN1-mutant PNETs. Here we show the MEN1-encoded scaffold protein menin regulates phosphorylation of β-catenin. β-catenin signalling is activated in MEN1-mutant human and mouse PNETs. Conditional knockout of β-catenin suppresses the tumorigenesis and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 44 publications
3
66
0
Order By: Relevance
“…These mouse models have shown that the expression of activated K-RAS(p.G12D) enhances rather than inhibits β-cell proliferation, β-catenin loss can suppress insulinoma tumorigenesis, histone demethylase retinoblastoma binding protein-2 (Rbp2) loss decreases insulinoma formation and prolongs survival, ActivinB loss prolongs survival, and MLL1/KMT2A loss leads to earlier onset of tumor formation (4 months vs. 6 months) and shortened lifespan by promoting tumor progression and angiogenesis (Chamberlain, et al 2014; Jiang, et al 2014; Lin, et al 2011; Lin, et al 2016; Ripoche, et al 2015). Such studies have dual benefits as they help to understand tumorigenesis and to reveal β-cell proliferation mechanisms for developing β-cell replacement strategies to help diabetic patients who suffer from functional β-cell loss (Garcia-Ocana and Stewart 2014).…”
Section: Genetically Engineered Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…These mouse models have shown that the expression of activated K-RAS(p.G12D) enhances rather than inhibits β-cell proliferation, β-catenin loss can suppress insulinoma tumorigenesis, histone demethylase retinoblastoma binding protein-2 (Rbp2) loss decreases insulinoma formation and prolongs survival, ActivinB loss prolongs survival, and MLL1/KMT2A loss leads to earlier onset of tumor formation (4 months vs. 6 months) and shortened lifespan by promoting tumor progression and angiogenesis (Chamberlain, et al 2014; Jiang, et al 2014; Lin, et al 2011; Lin, et al 2016; Ripoche, et al 2015). Such studies have dual benefits as they help to understand tumorigenesis and to reveal β-cell proliferation mechanisms for developing β-cell replacement strategies to help diabetic patients who suffer from functional β-cell loss (Garcia-Ocana and Stewart 2014).…”
Section: Genetically Engineered Mouse Modelsmentioning
confidence: 99%
“…Other potential treatment options targeted receptors associated with tumor angiogenesis (VEGF receptors) or specific somatostatin receptors. These pre-clinical studies include menin replacement therapy, an angiogenesis inhibitor (anti-VEGF-A monoclonal antibody, mAb G6–31), a small molecular tyrosine kinase inhibitor of all VEGF receptors (Sunitinib), a somatostatin analog (Pasireotide/SOM230), a Hedgehog pathway inhibitor GDC-0449, a β-catenin inhibitor PKF115–584, and an epigenetic drug (BET protein inhibitor JQ1) (Gurung, et al 2013b; Jiang et al 2014; Korsisaari, et al 2008; Lines, et al 2017; Quinn, et al 2012; Walls, et al 2012; Walls, et al 2016). …”
Section: Genetically Engineered Mouse Modelsmentioning
confidence: 99%
“…Ongoing research is currently investigating whether specific RET mutations could predict the success of treatment with receptor kinase inhibitors (NCT01945762) in MTC. Another hypothesis that needs to be tested is that mutations in genes involved in mTOR signaling could be used as biomarkers of rapalogue response (155,156).development of future therapies: both combination therapy with FAK and mTOR inhibitors (157) as well as inhibition of B-catenin in MEN1 deficient pancreatic NETs (158). Immunotherapy is also an emerging branch in cancer treatment where the knowledge of tumor genetics and biology has proved to be important for prediction.…”
Section: Authors Perspectives and Future Implicationsmentioning
confidence: 99%
“…Conditional knockout of β-catenin in Men1 -deficient mice leads to suppression of tumorigenesis and significantly improved hypoglycemia and the survival rate of the mice (Jiang, et al 2014). Antagonizing β-catenin signaling by the small molecule inhibitor PKF115–584 in Men1 -deficient mice also suppresses tumor cell proliferation in vitro and in vivo (Jiang et al 2014).…”
Section: Introductionmentioning
confidence: 99%